Manajemen Mutu Pembelajaran Kitab Kuning - Hidayah, Nurul (Universitas Muhammadiyah Yogyakarta, 2023)
Al-Iman Islamic Boarding School has long been known as one of the Islamic boarding schools in Purworejo which has formal educational institutions and excels in the field of yellow books. The graduating students have the ability to master the yellow book. Over time, Islamic boarding schools have experienced rapid development. Currently, Islamic boarding schools have formal educational institutions from early childhood education to tertiary level. The number of students continues to increase until it reaches three thousand. Under these conditions, quality management is needed in learning the yellow book so that the superiority of Islamic boarding schools as producers of students who are literate in the book can be maintained. This research aims to determine the quality management process in yellow book learning for Madrasah Tsanawiyah and Aliyah students. This research uses descriptive qualitative research methods by collecting data through interviews, observation and documentation. The research results show that the quality management process of yellow book learning is carried out in three stages, namely quality planning, quality control and quality improvement. Quality planning is carried out by determining graduate competency standards that must be mastered by students, identifying new students, identifying the needs of new students, designing the curriculum, system and daily schedule for learning the yellow book. Quality control is carried out by assessing the competency of students in mastering the yellow book, comparing these results with the competency standards of graduating students and adopting policies based on the results of the assessment. Quality improvement is carried out by evaluating the performance of yellow book learning, determining the necessary infrastructure, improving existing learning systems and creating new systems, forming education administrators, providing provision in the form of knowledge, training and motivation for new educational administrators, and monitoring performance. education administrator.Keywords: quality management; learning; yellow book.